Does male age have an influence on the risk of spontaneous abortion? An approach combining semiparametric and parametric regression - Rémy Slama; Axel Werwatz; Odile Boutou; Béatrice Ducot; Alfred Spira; Wolfgang Härdle (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
Couples from Western countries tend to delay their pregnancies, which may affect their ability to obtain a live birth. We assessed the association between male age and the risk of spontaneous abortion taking into account woman's age. We performed telephone interviews on a ross-sectional random population sample of 1124 French women who had been pregnant between 1985 and 2000, who described 2281 pregnancies, among which 290 (12.7%) ended by a spontaneous abortion. We used logistic regression and generalised partial linear models, a class of semiparametric regression models. Our final random effect logistic regression model predicted that, among women aged 25 years, the odds-ratio (OR) of spontaneous abortion associated with the male partner being older than 35 years, as compared to men younger than 35 years, was 2.48 (95% Confidence Interval (CI): [1.13-5.41]). No such effect of male age was observed when the woman was 35 years (OR=0.53, CI: [0.27-1.01]). Male age had on the whole no strong influence on the risk of spontaneous abortion, but exhibited an increased risk after 35 years, only among younger women. This possible effect should be further investigated, possibly in studies with assessment of the presence of chromosomal abnormalities in the abortus.
urn:nbn:de:kobv:11-10048897
Keywords: 330; Spontaneous abortion; foetal loss; man's age; semiparametric models; logistic; random effect